Formação de Acervo x Mineração: a coleção paleontológica do Museu Paraense Emílio Goeldi e sua relação com a mineração no município de Capanema-PA - SILVA, Rayana Alexandra Sousa da (2019)
In this paper, we analyze the relationship established between Paleontology and Mining, for the formation of museological collections, starting from the observation of the association between the collection of the Museu Paraense Emílio Goeldi (MPEG) and the mineral exploration in the municipality of Capanema-PA. This collection currently has 6,292 fossil specimens, of which 1,784 come directly from Capanema, being distributed among the four collections as follows: 22% paleoinvertebrates, 26% paleovertebrates, 6% paleobotanics and 11% microfossils, whose major origin consists of materials from Amazonian sedimentary deposits, especially the Pirabas Formation. Based on the importance that MPEG plays in the local, national and international context as an important museological institution, as well as the double role that the miners assume in the sense of preservation and what is destroyed for the production of goods like cement. For this, a quantitative and qualitative analysis of the composition of this collection is done, in order to reflect on issues such as: fossils as patrimony; the role of the museum as mediator of the relation man x paleontological patrimony; the safeguarding of these assets, based on musealization as a way of preserving cultural assets. It has been found that there is no fair measure between what is turned into merchandise and what is returned to society through the museum, since there is a huge disparity between the proportion of what goes into the collection and the annual tons converted into products. It was possible to reflect on the mitigating actions that are currently being carried out, as well as on the potentialities generated from the empowerment of the local community in relation to such assets.